The many faces of public management reform in the Asia-pacific region - Wescott, Clay; Phitthaya Bowonwatthana; Jones, Lawrence (Emerald, 2009)
During the past decade, globalization and democratization have been the major forces that helped transform the structures, functions, and processes of Asian public sectors. Nevertheless, these transformation efforts of Asian countries vary considerably depending on local context, and have met with different degrees of success. Some countries experienced smooth transformations. For others, the reform process has been more volatile. These issues were explored at a conference July 7-9, 2008 in Bangkok, Thailand, hosted by the Faculty of Political Science, Chulalongkorn University, and co-sponsored by the International Public Management Network, the Asia-Pacific Governance Institute, and Thailand Democracy Watch. This book presents some of the works contributed by participating scholars and practitioners at the conference. The contents fall into three categories: corruption and anti-corruption initiatives, public financial management reforms, and public management reforms with emphasis on performance and results.
Keywords: Public administration.; elektronické knihy; electronic books